Design and evaluation of an actuated knee implant for postoperative ligament imbalance correction. Issue 4 (April 2016) - Collo, A.; Almouahed, S.; Poignet, P.; Hamitouche, C.; Stindel, E.
Highlights: Postoperative knee ligament laxity can be compensated without revision surgery. The knee implant tibial component embeds a miniaturised actuation system. Stability and force sensors tests were carried out on a knee simulator. The effectiveness of the proposed design was assessed under normal working conditions. Abstract: In Total Knee Arthroplasty (TKA), the collateral ligament tensioning stage cannot be standardised for all patients and relies heavily on the surgeon's experience and perception. Intraoperative inaccuracies are practically unavoidable and may give rise to severe postoperative complications, leading to the need for revision surgery already a few years after primary TKA. This work proposes a novel instrumented tibial component able to detect collateral ligament laxity conditions right after primary TKA and, if needed, to compensate for them in the postoperative period. A miniaturised actuation system, designed to be embedded in the tibial baseplate, was initially evaluated by means of 3D simulations and then fabricated as a full-scale prototype. Stability and force sensors tests carried out on a knee simulator allowed to assess the effectiveness of the proposed design under normal working conditions and provided valuable insights for future work and improvements.